Ritmo de trabalho no setor de costura em pequenas empresas de confecção - Herculani, Rhadler (2007)
The objective of the dissertation is studying the pace of work in the sector of small sewing businesses of textile manufacturing. This sector has great socio-economic importance for Brazil, because of their economic contribution, as well as the quantity of jobs created. To achieve the proposed objective, was first performed a literature review on pace and organization of work, taking into consideration the factors that affect the pace of work in general, such as technology, training and motivation of staff, among others. Then, there was a review of the literature on small business, construction, highlighting its history, technology, industrial processes and general labor. The following are presented in 3 case studies of small businesses in construction, seeking to deepen the knowledge about factors that influence the pace of work. Finally, the study concludes the importance of human labor and industry of sewing, emphasizing that the pace remains influenced by good working conditions.